2008
DOI: 10.1167/iovs.08-2748
|View full text |Cite
|
Sign up to set email alerts
|

Palisade Endings: Cholinergic Sensory Organs or Effector Organs?

Abstract: The present study ascertained that palisade endings are cholinergic motor organs. Therefore, it was concluded that palisade endings are not candidates to provide eye-position signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 18 publications
7
61
1
Order By: Relevance
“…In later studies of other species, the same authors ascertained that the structures in question are pure cholinergic motor organs arising from axons that also supply the associated MIF. [27][28][29][30] They hence argued, in contrast to previous studies, 31 that surgical strabismus procedures should have no side effects with respect to eye-position signals. 30 Other studies, using central tracer injections in non-human primates, also support a motor function, but suggest that tendon endings and 'en grappe' terminals arise from separate neurons located around the periphery of the motor nuclei of EOMs.…”
Section: Myotendinous Nerve Endingsmentioning
confidence: 89%
See 2 more Smart Citations
“…In later studies of other species, the same authors ascertained that the structures in question are pure cholinergic motor organs arising from axons that also supply the associated MIF. [27][28][29][30] They hence argued, in contrast to previous studies, 31 that surgical strabismus procedures should have no side effects with respect to eye-position signals. 30 Other studies, using central tracer injections in non-human primates, also support a motor function, but suggest that tendon endings and 'en grappe' terminals arise from separate neurons located around the periphery of the motor nuclei of EOMs.…”
Section: Myotendinous Nerve Endingsmentioning
confidence: 89%
“…[27][28][29][30] They hence argued, in contrast to previous studies, 31 that surgical strabismus procedures should have no side effects with respect to eye-position signals. 30 Other studies, using central tracer injections in non-human primates, also support a motor function, but suggest that tendon endings and 'en grappe' terminals arise from separate neurons located around the periphery of the motor nuclei of EOMs. 32,33 Even though it cannot be precluded that myotendinous nerve endings have a sensory function, 2,34 the notion that muscle spindles represents the only structures with proprioceptive potency seem to gain growing support.…”
Section: Myotendinous Nerve Endingsmentioning
confidence: 89%
See 1 more Smart Citation
“…Investigation of molecular phenotypes revealed that palisade endings are cholinergic structures (Blumer et al, 2009), and tracing studies located their cell body in close proximity to oculomotor nuclei (Lienbacher et al, 2011a;Zimmermann et al, 2011). In addition, immunoreactivity of nicotinic acetylcholine receptors by ␣-bungarotoxin has shown that a substantial minority of palisade ending axons form sequential motor terminals along the muscle body before establishing tendinous terminations (Blumer et al, 2009).…”
Section: Review Of Zimmermann Et Almentioning
confidence: 99%
“…Observations of nerve terminals with efferent features have led some authorities to promote that these structures form part of the conventional motor innervations of the MIFs (Blumer et al, 2009). An alternative view is that the efferent innervations may tune the sensitivity of the receptor in a similar manner as the efferent innervations adjusting the intrafusal fibres in spindles.…”
Section: Sensory Receptorsmentioning
confidence: 99%